2015
DOI: 10.1002/14651858.cd010070.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Altered dietary salt intake for people with chronic kidney disease

Abstract: Analysis 1.1. Comparison 1 Net change with altering salt and change by duration, Outcome 1 Sodium excretion. . Analysis 1.2. Comparison 1 Net change with altering salt and change by duration, Outcome 2 Systolic blood pressure. Analysis 1.3. Comparison 1 Net change with altering salt and change by duration, Outcome 3 Diastolic blood pressure. Analysis 1.4. Comparison 1 Net change with altering salt and change by duration, Outcome 4 eGFR [mL/min/1.73 m2]. Analysis 1.5. Comparison 1 Net change with altering salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
117
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 61 publications
5
117
0
2
Order By: Relevance
“…Only few studies have described the impact of lifestyle improvements on kidney outcomes. Some evidence exists on the positive effect of salt reduction on both hypertension and proteinuria in people with CKD [30] and of smoking cessation on kidney function [31]. However, within these studies the outcomes were limited to proteinuria and kidney function instead of hard renal outcomes such as end stage renal disease [11].…”
Section: Implementation Of Lifestyle Measuresmentioning
confidence: 99%
“…Only few studies have described the impact of lifestyle improvements on kidney outcomes. Some evidence exists on the positive effect of salt reduction on both hypertension and proteinuria in people with CKD [30] and of smoking cessation on kidney function [31]. However, within these studies the outcomes were limited to proteinuria and kidney function instead of hard renal outcomes such as end stage renal disease [11].…”
Section: Implementation Of Lifestyle Measuresmentioning
confidence: 99%
“…48,49 In CKD, this reduction in BP was accompanied by a reduction in proteinuria. 50 As such, reduced salt diets are recommended in children with HTN and CKD. 50 Obesity and metabolic syndrome: risk factors for CKD in the pediatric population Obesity in children continues to be on the rise, with a predicted increase of 40% in the next decade.…”
Section: Salt Intake Htn and Ckdmentioning
confidence: 99%
“…50 As such, reduced salt diets are recommended in children with HTN and CKD. 50 Obesity and metabolic syndrome: risk factors for CKD in the pediatric population Obesity in children continues to be on the rise, with a predicted increase of 40% in the next decade. 51 The National Health and Nutrition Examination Survey data showed that …”
Section: Salt Intake Htn and Ckdmentioning
confidence: 99%
“…In 2015, McMahon et al [44] performed a systematic review including the results of 8 randomized controlled trials, with a total of 258 patients included, the average study duration being 6 weeks (summarized in Table 1). Five were performed in CKD patients with heterogeneous intervention methods, and most mostly including patients in early stages of CKD.…”
Section: Impact Of Sodium Intake Lowering and CV And Kidney Disease Riskmentioning
confidence: 99%
“…Five were performed in CKD patients with heterogeneous intervention methods, and most mostly including patients in early stages of CKD. Interestingly, reducing sodium intake was consistently associated with a decrease in BP by 8/3 mm Hg mirrored by a drop in proteinuria ranging from 20 to 50% [44]. …”
Section: Impact Of Sodium Intake Lowering and CV And Kidney Disease Riskmentioning
confidence: 99%